Entrepreneurship, Regional Development and Job Creation: the Case of Portugal - Rui Baptista; Vítor Escária; Paulo Madruga (Max Planck Institute for Research into Economic Systems, 2005)
This paper investigates whether a high level of new business formation in a region stimulates employment in that region. The study looks at the lag structure of these effects, using a data set covering a fairly large time span (1982-2002). The indirect supply-side effects of new firm births, whether due to greater competition, efficiency or innovation, seem to be at least as important as the direct effects associated with employment creation by the new entrants. However, such supply-side effects only occur after a time lag of about eight years, leading to a pattern of lagged effects that is somewhat u-shaped. This finding suggests that new entrants bring about improvements to overall regional competitiveness, but that such improvements only become significant after some time.
Keywords: 330; Unternehmensgründung; Beschäftigungseffekt; Regionale Entwicklung; Portugal